2018
DOI: 10.1074/jbc.ra118.001696
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis PPE60 antigen drives Th1/Th17 responses via Toll-like receptor 2–dependent maturation of dendritic cells

Abstract: Targeting of (MTB) PE/PPE antigens that induce type 1 helper T cell (Th1) and Th17 responses represents a crucial strategy for the development of tuberculosis (TB) vaccines. However, only a few PE/PPE antigens induce these responses. Here, we sought to determine how the cell wall-associated antigen PPE60 (Rv3478) activates dendritic cell (DC) maturation and T-cell differentiation. We observed that PPE60 induces DC maturation by augmenting the protein expression of cluster of differentiation 80 (CD80) and CD86 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…This mouse model was not available in our laboratory. Instead, we observed that MAP1889c-matured DC could induce T cell proliferation when antigen-activated DCs were co-cultured with splenic T cells from Ag85B-immunized mice followed by the addition of Ag85B to the culture media ( Figure 6) as described previously [42]. We confirmed that MAP1889c-matured DCs could induce Th2 responses in vitro.…”
Section: Discussionsupporting
confidence: 86%
“…This mouse model was not available in our laboratory. Instead, we observed that MAP1889c-matured DC could induce T cell proliferation when antigen-activated DCs were co-cultured with splenic T cells from Ag85B-immunized mice followed by the addition of Ag85B to the culture media ( Figure 6) as described previously [42]. We confirmed that MAP1889c-matured DCs could induce Th2 responses in vitro.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, NT03MA4150, an ortholog of the Mtb MPTR subfamily gene rv0442c, was the only MPTR ortholog without the characteristic polymorphic MPTR C-terminal region identified in the genome of M. avium subsp. 2.2 | The pe/ppe genes are essential for the in vivo and in vitro survival of Mtb Studies have shown that PE/PPE family proteins were associated with the survival of Mtb in vivo and in vitro through regulation of the host immune response (Grover et al, 2018;Su et al, 2018). PPE60…”
Section: The Pe/ppe Genes Are Associated With Mycobacterial Pathogementioning
confidence: 99%
“…However, knock-out of TLR2 did not completely abrogate the expression of NLRP3 protein and the secretion of IL-1β induced by PPE60, indicating that other receptors may contribute to NLRP3 inflammasome activation. 46 Interestingly, we found that PPE13 can directly interact with NLRP3 protein, but not with ASC and caspase-1.…”
Section: F I G U R E 4 Ppe13mentioning
confidence: 74%